The effect of oral isotretinoin therapy on meibomian gland morphology and dry eye tests. (17th February 2022) - Düzgün, Eyüp; Özkur, Ezgi
Abstract: Purpose: The aim of study was to evaluate the effects of oral isotretinoin on meibomian gland (MG) morphology detected with non-contact meibography and to investigate its relation with clinical dry eye tests. Methods: Forty-five acne patients treated with isotretinoin underwent a full ophthalmological examination at baseline and in the fourth month as follows: ocular surface disease index (OSDI) questionnaire, assessments of tear film break-up time (TFBUT), corneal fluorescein staining, Schirmer test, meibum expression, and lid margin abnormalities. Non-contact meibography imaging and noninvasive tear break up time (NI-BUT) assessments were also performed. The changes in MGs were scored (meibography score) as grade 0, no change; grade 1, mild; grade 2, moderate; and grade 3, marked. Results: There was a statistically significant change in OSDI, corneal fluorescein staining, lid margin abnormality, and meibum expression score during the treatment compared to baseline values ( p < .001, p = .02, p < .001, and p < .001, respectively). All meibography scores showed a positive correlation with the lid margin abnormality and meibum expression score but did not correlate with the TFBUT, NI-BUT, Schirmer test, or the corneal fluorescein staining score. Conclusion: The morphologic analysis using non-contact meibography is a useful method for assessing isotretinoin-related changes in MGs.